Lithium-sulfur batteries with improved energy density and power output.
By optimizing the mass ratio of sulfur to electrolyte and the loading value of sulfur in lithium-sulfur batteries, the energy density and maximum output are significantly enhanced, addressing the limitations of existing lithium-sulfur batteries for high-demand applications.
Patent Information
- Application Number
- JP2023554367
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-23
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2042-10-26
AI Technical Summary
Lithium-sulfur batteries face challenges in achieving high energy density and output due to the low output resulting from the electrochemical conversion reaction of sulfur in the positive electrode active material, which limits their application in high-demand systems like Urban Air Mobility aircraft.
The lithium-sulfur battery design is optimized by setting the mass ratio of sulfur in the positive electrode to the mass of the electrolyte (ES/L) within the range of 1 to 1.4, and the loading value of sulfur (L) within 2 to 2.6 mAh/cm², to achieve a balance between energy density and maximum output.
This optimized design allows the lithium-sulfur battery to achieve an energy density of 300 Wh/kg or more and a maximum output of 2 kW/kg or more, meeting the requirements for advanced applications such as Urban Air Mobility aircraft.
Smart Images

Figure 0007657956000003 
Figure 0007657956000004 
Figure 0007657956000005
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0161896 filed on November 23, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.
[0002] The present invention relates to a lithium-sulfur battery having improved energy density and output, and more particularly, to a lithium-sulfur battery having improved energy density and output, which can simultaneously realize an energy density per battery weight of 300 Wh / kg or more and a maximum output of 2 kW / kg or more by setting the mass ratio of sulfur in a positive electrode to the mass of an electrolyte and the loading value of sulfur in the positive electrode within specific ranges. [Background technology]
[0003] As interest in energy storage technology continues to grow, the fields of application are expanding to include mobile phones, tablets, laptops, and camcorders, as well as the energy of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and research and development of electrochemical devices is gradually increasing. Electrochemical devices are the field that is attracting the most attention in this regard, and among them, the development of secondary batteries such as rechargeable lithium-sulfur batteries is attracting attention, and recently, the development of such batteries has led to research and development of new electrodes and battery designs to improve capacity density and specific energy.
[0004] Such electrochemical devices, including Li-S batteries, which use sulfur as the positive electrode active material, have a high specific energy density per unit weight and are attracting attention as a next-generation secondary battery that can replace lithium-ion batteries. In such lithium-sulfur batteries, a reduction reaction of sulfur and an oxidation reaction of lithium metal occur during discharge, at which time sulfur changes from a ring-structured S8 to a linear-structured lithium polysulfide (LiPS), and such lithium-sulfur batteries are characterized by showing a stepwise discharge voltage until the polysulfide is completely reduced to Li2S.
[0005] However, one of the obstacles to the commercialization of lithium-sulfur batteries is their low output due to the electrochemical conversion reaction of sulfur contained in the positive electrode active material. On the other hand, existing lithium-ion batteries operate through an intercalation reaction in which lithium ions are inserted into the positive electrode / negative electrode structure, and have relatively higher output than lithium-sulfur batteries. However, as mentioned above, lithium-sulfur batteries (Li-S batteries) have the advantage of having a high energy density per unit weight, even compared to lithium-ion batteries.
[0006] Therefore, the design of lithium-sulfur batteries needs to be changed to have maximum output at the same energy density per weight. In particular, for application to aircraft used in service systems such as Urban Air Mobility (UAM), the energy density per unit weight needs to be increased to 300Wh / kg or more (lithium-ion batteries are less than 300Wh / kg), and at the same time, the maximum output needs to be increased to the normally required 2kW / kg or more. Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to provide a lithium-sulfur battery having improved energy density and output, which can simultaneously realize an energy density per battery weight of 300 Wh / kg or more and a maximum output of 2 kW / kg or more by setting the mass ratio of sulfur in the positive electrode to the mass of the electrolyte and the sulfur loading value in the positive electrode within specific ranges. [Means for solving the problem]
[0008] To achieve the above object, the present invention provides a lithium-sulfur battery that includes a positive electrode containing sulfur as a positive electrode active material, a lithium metal negative electrode, and an electrolyte, and satisfies the following Equation 1:
[0009] [Formula 1] 1≦ES / L≦1.4 In Equation 1, ES is the mass (g) of the electrolyte divided by the mass (g) of sulfur contained in the positive electrode, and L is the sulfur loading value for the positive electrode, expressed in mAh / cm. 2 It is. Effect of the Invention
[0010] The lithium-sulfur battery having improved energy density and output according to the present invention has an advantage in that it can simultaneously realize an energy density per battery weight of 300 Wh / kg or more and a maximum output of 2 kW / kg or more by setting the mass ratio of sulfur in the positive electrode to the mass of the electrolyte and the sulfur loading value for the positive electrode within a specific range. [Brief description of the drawings]
[0011] [Figure 1] 1 is a graph showing ES / L values depending on sulfur loading values for a positive electrode. [Diagram 2] 1 is a graph showing ES / L values depending on sulfur loading values for a positive electrode. [Diagram 3] 1 is a graph showing the energy density and power output of a lithium-sulfur battery in conjunction with the ES / L value. [Figure 4]1 is a graph showing the power output of a lithium-sulfur battery in relation to the ES / L value. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below.
[0013] The lithium-sulfur battery having improved energy density and output according to the present invention includes a positive electrode containing sulfur as a positive electrode active material, a lithium metal negative electrode, and an electrolyte, and is characterized by satisfying the following Equation 1:
[0014] [Formula 1] 1≦ES / L≦1.4
[0015] In Equation 1, ES is the mass (g) of the electrolyte divided by the mass (g) of sulfur contained in the positive electrode, and L is the sulfur loading value for the positive electrode, expressed in mAh / cm. 2 It is.
[0016] Among electrochemical elements, lithium-sulfur batteries (Li-S batteries), which use sulfur as the positive electrode active material, have a high specific energy density per unit weight and are attracting attention as a next-generation secondary battery that can replace lithium-ion batteries. However, lithium-sulfur batteries have a problem with low output due to the electrochemical conversion reaction of sulfur contained in the positive electrode active material. In contrast, existing lithium-ion batteries proceed through an intercalation reaction in which lithium ions are inserted into the positive electrode / negative electrode structure, and have the advantage of relatively high output compared to lithium-sulfur batteries. However, as mentioned above, lithium-sulfur batteries (Li-S batteries) have the advantage of having a high energy density per unit weight, even compared to lithium-ion batteries (the energy density per weight of lithium-ion batteries is less than 300Wh / kg).
[0017] Therefore, the applicant has modified the design of the lithium-sulfur battery to provide maximum output at the same energy density per unit weight, and has developed a lithium-sulfur battery that has an energy density per unit weight of 300Wh / kg or more for application in aircraft such as Urban Air Mobility (UAM), while at the same time increasing the maximum output to the normally required 2kW / kg or more.
[0018] The present invention will now be described in more detail.
[0019] As described above, the lithium-sulfur battery having improved energy density and power output of the present invention satisfies the following Equation 1:
[0020] [Formula 1] 1≦ES / L≦1.4
[0021] In the above formula 1, ES is the mass (g) of the electrolyte divided by the mass (g) of sulfur contained in the positive electrode, and L (unit: mAh / cm 2 ) is the sulfur loading value for the positive electrode. If the ES / L value is less than 1, the electrolyte content is reduced, causing a large overvoltage and a sudden decrease in output. If the ES / L value is more than 1.4, the energy density per unit weight of the battery is reduced.
[0022] At this time, the ES value is preferably within the range of 2≦ES<3.7. Also, the L value is preferably within the range of 2≦L≦2.6. Therefore, if the L value is 2, the ES value must be within the range of 2≦ES≦2.8, and if the L value is 2.6, the ES value must be within the range of 2.6≦ES≦3.64. If the ES value is less than 2, the energy density of the battery may be high, but the output power drops sharply. Also, if the ES value is 3.7 or more, the output power of the battery may be high, but the energy density is not higher than that of a lithium-ion battery (less than 300Wh / kg).
[0023] As described above, when the ES / L value range is set to be within the range of 1≦ES / L≦1.4, the energy density of the lithium-sulfur battery is 300Wh / kg or more, and the maximum output is 2kW / kg or more, which is generally required, resulting in a lithium-sulfur battery with the same energy density per unit weight and maximum output. Specific experimental data related to this will be shown in the examples below.
[0024] More specifically, if the L value is 2≦L<2.5, the energy density of the battery is 300Wh / kg or more and less than 350Wh / kg. The output value at this time is 2 to 2.6kW / kg. If the L value is 2.5≦L≦2.6, the energy density of the battery is 300 to 350Wh / kg. The output value at this time is more than 2kW / kg to 2.6kW / kg. If the ES / L value is 1 and the L value is 2.5≦L≦2.6, the energy density of the battery is 350Wh / kg. The output value at this time is more than 2kW / kg to 2.3kW / kg.
[0025] The electrolyte, the positive electrode, the negative electrode and the separator contained in the lithium-sulfur battery of the present invention will now be described in detail.
[0026] First, the electrolyte included in the lithium-sulfur battery of the present invention includes a first solvent, a second solvent, and a lithium salt. The first solvent includes a heterocyclic compound including one or more double bonds and at the same time, either an oxygen atom or a sulfur atom, and has a characteristic of being difficult to dissolve salt due to delocalization of lone pair electrons of the heteroatom (oxygen atom or sulfur atom). Therefore, during the initial discharge stage of the battery, a polymer protective film (solid electrolyte interface, SEI layer) is formed on the surface of the lithium-based metal (negative electrode) through a ring opening polymerization reaction of the heterocyclic compound, thereby suppressing the generation of lithium dendrites, and further reducing electrolyte decomposition on the surface of the lithium-based metal and the resulting side reactions, thereby improving the life characteristics of the lithium-sulfur battery.
[0027] That is, the heterocyclic compound of the present invention contains one or more double bonds to form a polymer protective film on the surface of the lithium-based metal, and also contains a heteroatom (oxygen atom or sulfur atom) to impart polarity and exert effects such as increasing affinity with other solvents in the electrolyte.
[0028] The heterocyclic compound may be a 3-15 membered, preferably 3-7 membered, more preferably 5-6 membered heterocyclic compound. The heterocyclic compound may be a heterocyclic compound substituted or unsubstituted with one or more selected from the group consisting of an alkyl group having 1 to 4 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group (-NO2), an amine group (-NH2) and a sulfonyl group (-SO2). The heterocyclic compound may be a multi-ring compound of a heterocyclic compound and one or more of a cyclic alkyl group having 3 to 8 carbon atoms and an aryl group having 6 to 10 carbon atoms.
[0029] When the heterocyclic compound is substituted with an alkyl group having 1 to 4 carbon atoms, the radical is stabilized, and side reactions with the electrolyte are preferably suppressed. When the heterocyclic compound is substituted with a halogen group or a nitro group, a functional protective film can be formed on the surface of the lithium-based metal, and the formed functional protective film is stable as a compact protective film, which has the advantage of enabling uniform deposition of the lithium-based metal and suppressing side reactions between the polysulfide and the lithium-based metal.
[0030] Specific examples of the heterocyclic compound include furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, and benzofuran. ofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene, among which 2-methylfuran is preferably used as the first solvent.
[0031] The first solvent containing such a heterocyclic compound may be included in the electrolyte for lithium secondary batteries of the present invention in a volume ratio of 5 to less than 95, preferably 10 to 80, more preferably 15 to 60, based on 100 volume ratios of the total organic solvents (i.e., first solvent + second solvent) (the remaining volume ratio corresponds to the second solvent). If the first solvent is included in an amount of less than 5 volume ratios based on 100 volume ratios of the total organic solvents of the electrolyte, the ability to reduce the amount of polysulfide gushing out may be reduced, and the resistance increase of the electrolyte may not be suppressed, or a problem may occur in which a protective film is not completely formed on the surface of the lithium-based metal. In addition, if the first solvent is included in an amount of 95 volume ratios or more based on 100 volume ratios of the total organic solvents of the present invention, the surface resistance of the electrolyte and the lithium-based metal may increase, resulting in a problem of reduced capacity and lifespan of the battery.
[0032] The second solvent includes at least one of an ether-based compound, an ester-based compound, an amide-based compound, and a carbonate-based compound, and dissolves a lithium salt to allow the electrolyte to have lithium ion conductivity, and also releases sulfur, which is a positive electrode active material, to smoothly carry out an electrochemical reaction with lithium. In the case of the carbonate-based compound, it may be a linear carbonate-based compound or a cyclic carbonate-based compound.
[0033] Specific examples of the ether-based compound include one or more selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether, but are not limited thereto. Among these, it is preferable to use dimethoxyethane as the second solvent.
[0034] The ester compound may be, but is not limited to, one or more selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone. The amide compound may be a conventional amide compound used in the art.
[0035] In addition, examples of the linear carbonate compound include one or more compounds selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethylmethyl carbonate (EMC), methylpropyl carbonate (MPC) and ethylpropyl carbonate (EPC), but are not limited thereto.
[0036] In addition, examples of the cyclic carbonate compound include one or more compounds selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof (e.g., fluoroethylene carbonate (FEC)), but are not limited thereto.
[0037] The lithium salt is an electrolyte salt used to increase ion conductivity and may be any salt commonly used in the art. Specific examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium aliphatic carboxylate having 4 or less carbon atoms, lithium tetraphenylborate, and lithium imide may be exemplified, and among these, it is preferable to include LiFSI ((SO2F)2NLi). At the same time, as one embodiment of the present invention, the electrolyte may be in a form that does not include LiTFSI ((CF3SO2)2NLi).
[0038] The concentration of the lithium salt may be determined in consideration of ion conductivity, and may be, for example, 0.1 to 4 M, preferably 0.2 to 2 M, and more preferably 0.5 to 2 M. If the concentration of the lithium salt is below the above range, it may be difficult to ensure ion conductivity suitable for battery operation, and if the concentration exceeds the above range, the viscosity of the electrolyte may increase, decreasing the mobility of lithium ions, or the decomposition reaction of the lithium salt itself may increase, decreasing the performance of the battery.
[0039] In addition, the lithium salt may be included in an amount of 2 to 45 wt %, preferably 4 to 30 wt %, and more preferably 8 to 25 wt % based on the total weight of the electrolyte. If the lithium salt is included in an amount of less than 2 wt % based on the total weight of the electrolyte, the lithium ion conductivity may be insufficient, causing a problem of increased resistance to ion transfer. If the lithium salt is included in an amount of more than 45 wt %, the lithium ion conductivity may decrease and at the same time, the viscosity of the electrolyte may increase, causing a problem of increased mass transfer resistance.
[0040] In addition, the electrolyte contained in the lithium-sulfur battery of the present invention may further contain one or more additives selected from the group consisting of lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), lithium nitrite (LiNO2), potassium nitrite (KNO2), and cesium nitrite (CsNO2), as necessary.
[0041] Next, the positive electrode included in the lithium-sulfur battery of the present invention includes a positive electrode active material and a binder, but does not include a conductive material that is commonly used together with the positive electrode active material and the binder, so that a lithium-sulfur battery having an energy density of 300 Wh / kg or more can be realized. In other words, the positive electrode includes a positive electrode active material and a binder, but does not include a conductive material other than the carbon material included in the positive electrode active material. Also, the positive electrode may be a base solid content including the positive electrode active material and the binder located on a current collector.
[0042] The positive electrode active material may be a material applicable to a conventional lithium-sulfur battery, and may include, for example, elemental sulfur (S8), a sulfur-based compound, or a mixture thereof. Specifically, the sulfur-based compound may be Li2S n (n ≥ 1), organic sulfur compounds or sulfur-carbon complexes ((C2S x ) n (x=2.5 to 50, n≧2), etc. The positive electrode active material preferably contains a sulfur-carbon composite.
[0043] The sulfur-carbon composite may have a particle size of 1 to 100 μm. If the particle size of the sulfur-carbon composite is less than 1 μm, the resistance between particles may increase, which may cause overvoltage in the electrode of the lithium-sulfur battery. If the particle size of the sulfur-carbon composite is more than 100 μm, the surface area per unit weight may be reduced, which may reduce the wetting area with the electrolyte in the electrode and the reaction site with lithium ions, resulting in a reduced amount of electron transfer relative to the size of the composite, which may slow down the reaction, and may reduce the discharge capacity of the battery.
[0044] The sulfur (S) may be included in an amount of 60 to 80 wt %, preferably 67.5 to 75 wt %, based on the total weight of the positive electrode. The sulfur content in the positive electrode of a conventional lithium-sulfur battery is about 40 to 60 wt % based on the total weight of the positive electrode, and the present invention uses sulfur at a much higher content than this, but shows an initial discharge capacity of about 1,550 mAh / g or more under the electrolyte conditions of the present invention. If the sulfur is used in an amount less than 60 wt % based on the total weight of the positive electrode, a problem of a decrease in the energy density of the battery may occur, and if it is used in an amount exceeding 80 wt %, a problem of a decrease in the conductivity in the electrode and a decrease in the stability of the electrode may occur.
[0045] The carbon material (or sulfur carrier) constituting the sulfur-carbon composite has porosity. In particular, the carbon material used as the positive electrode active material of the present invention has a high specific surface area (3,000 m 2 / g or more) and high porosity (Pore Volume: 0.7-3cm 3 / g), the electrolyte allows for high-capacity (1,575 to 1,675 mAh / g) operation.
[0046] The porous carbon material is 0.7 to 3 cm 3 The carbonaceous materials having a pore volume of 0.7 to 3 cm / g can be exemplified. 3Graphite that fills a pore volume of 1000 nm / g; graphene; reduced graphene oxide (rGO); carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon nanotubes (CNT) such as single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT); carbon fibers such as graphite nanofibers (GNF), carbon nanofibers (CNF), and activated carbon fibers (ACF); and activated carbon; and the like may be shaped like a sphere, a rod, a needle, a plate, a tube, or a bulk.
[0047] The cathode active material containing sulfur and carbonaceous material may be included in an amount of 80 to 99 parts by weight, preferably 85 to 97 parts by weight, based on 100 parts by weight of the total cathode weight. If the amount of the cathode active material is less than 80 parts by weight based on 100 parts by weight of the total cathode weight, the energy density of the battery may decrease, and if the amount is more than 99 parts by weight, the stability of the electrode may decrease.
[0048] The binder is a component that helps bind the positive electrode active material and the current collector, and may be, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polyvinylpyrrolidone, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butylene rubber, fluororubber, carboxymethylcellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, and mixtures thereof, but is not necessarily limited thereto.
[0049] The binder may be added in an amount of 1 to 15 parts by weight based on 100 parts by weight of the total weight of the positive electrode. If the content of the binder is less than 1 part by weight, the adhesive strength between the positive electrode active material and the current collector may be insufficient, and if the content of the binder is more than 15 parts by weight, the adhesive strength is improved, but the content of the positive electrode active material is accordingly reduced, resulting in a lower battery capacity.
[0050] In addition, a filler may be selectively added to the positive electrode of the present invention as a component for suppressing the expansion of the electrode. Such a filler is not particularly limited as long as it can suppress the expansion of the electrode without causing a chemical change in the battery, and examples of such a filler include olefin polymers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber; and the like.
[0051] The positive electrode may be manufactured by dispersing and mixing the positive electrode active material and the binder in a dispersion medium (solvent) to prepare a slurry, applying the slurry onto a positive electrode current collector, and then drying and rolling the slurry. The dispersion medium may be, but is not limited to, NMP (N-methyl-2-pyrrolidone), DMF (dimethyl formamide), DMSO (dimethyl sulfoxide), ethanol, isopropanol, water, or a mixture thereof.
[0052] The positive electrode current collector may be, but is not limited to, platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (In doped SnO2), FTO (F doped SnO2), and alloys thereof, and aluminum (Al) or stainless steel surface-treated with carbon (C), nickel (Ni), titanium (Ti), or silver (Ag). The positive electrode current collector may be in the form of a foil, a film, a sheet, a punched piece, a porous body, a foam, or the like.
[0053] The negative electrode is a lithium-based metal, and may further include a current collector on one side of the lithium-based metal. The current collector may be a negative electrode current collector. The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be selected from the group consisting of copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy, or may be a non-conductive polymer or a conductive polymer surface-treated with a conductive material. In general, a copper thin plate is used as the negative electrode current collector.
[0054] In addition, various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. with or without fine unevenness on the surface can be used. In addition, the negative electrode current collector is applied to have a thickness in the range of 3 to 50 μm. If the thickness of the negative electrode current collector is less than 3 μm, the current collecting effect is reduced, while if the thickness exceeds 50 μm, there is a problem that the processability is reduced when assembling the cell by folding.
[0055] The lithium-based metal may be lithium or a lithium alloy. In this case, the lithium alloy may include an element capable of being alloyed with lithium, and may be, specifically, an alloy of lithium and at least one selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al. The lithium-based metal may be in the form of a sheet or foil, and may be in the form of lithium or a lithium alloy deposited or coated on a current collector by a dry process, or in the form of particulate metal and alloy deposited or coated by a wet process, etc.
[0056] A conventional separator may be interposed between the positive electrode and the negative electrode. The separator is a physical separator having a function of physically separating the electrodes, and may be any separator that is used in conventional separators without any particular limitations. In particular, the separator is preferably one that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte. In addition, the separator separates or insulates the positive electrode and the negative electrode from each other, allowing lithium ions to be transported between the positive electrode and the negative electrode. Such a separator may be made of a porous, non-conductive or insulating material. The separator may be an independent member such as a film, or a coating layer added to the positive electrode and / or the negative electrode.
[0057] Examples of polyolefin-based porous membranes that can be used as the separation membrane include membranes formed of polyolefin-based polymers such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene), polypropylene, polybutylene, polypentene, etc., either alone or in combination. Examples of nonwoven fabrics that can be used as the separator include nonwoven fabrics made of polymers such as polyphenyleneoxide, polyimide, polyamide, polycarbonate, polyethyleneterephthalate, polyethylenenaphthalate, polybutyleneterephthalate, polyphenylenesulfide, polyacetal, polyethersulfone, polyetheretherketone, and polyester, either alone or in combination. Such nonwoven fabrics are in the form of fibers forming a porous web, and include spunbond or meltblown fabrics made of long fibers.
[0058] The thickness of the separator is not particularly limited, but is preferably in the range of 1 to 100 μm, and more preferably in the range of 5 to 50 μm. If the thickness of the separator is less than 1 μm, the mechanical properties cannot be maintained, and if it exceeds 100 μm, the separator acts as a resistance layer, resulting in a decrease in battery performance. The pore size and porosity of the separator are not particularly limited, but the pore size is preferably 0.1 to 50 μm and the porosity is preferably 10 to 95%. If the pore size of the separator is less than 0.1 μm or the porosity is less than 10%, the separator acts as a resistance layer, and if the pore size is more than 50 μm or the porosity is more than 95%, the mechanical properties cannot be maintained.
[0059] The lithium-sulfur battery of the present invention including the above-mentioned electrolyte, positive electrode, negative electrode, and separator may be manufactured by a process of placing a positive electrode and a negative electrode facing each other, interposing a separator therebetween, and then injecting an electrolyte.
[0060] Meanwhile, the lithium-sulfur battery according to the present invention can be applied to a battery cell used as a power source for a small device, and can be particularly suitable for use as a unit battery of a battery module that is a power source for a medium- to large-sized device. In this respect, the present invention also provides a battery module including two or more lithium-sulfur batteries electrically connected (series or parallel). The number of lithium-sulfur batteries included in the battery module can be variously adjusted in consideration of the use and capacity of the battery module. Furthermore, the present invention provides a battery pack in which the battery modules are electrically connected according to a conventional technique in the art. The battery module and the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle (HEV), and an electric plug-in hybrid electric vehicle (PHEV); an electric truck; an electric commercial vehicle; or a power storage system, but is not necessarily limited thereto. However, the lithium-sulfur battery of the present invention is preferably an aircraft battery used in Urban Air Mobility (UAM).
[0061] Hereinafter, preferred examples will be presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. It is natural that such changes and modifications fall within the scope of the appended claims.
[0062] [Production Example] Lithium-sulfur battery manufacturing Electrolyte production First, an electrolyte was prepared by dissolving LiFSI (lithium salt) in an organic solvent containing 2-methylfuran (first solvent) and dimethoxyethane (second solvent) in a volume ratio (v / v) of 5:5 to a concentration of 0.75M.
[0063] Cathode Manufacturing The positive electrode active material was a sulfur-carbon composite (S:C = 70:30 weight ratio) of 95 parts by weight (the content of sulfur alone was set to 67.5% by weight based on the total weight of the positive electrode, and the carbon material had a pore volume of 1.8 cm 3 A positive electrode slurry composition was prepared by mixing 5 parts by weight of activated carbon (w / g) and 5 parts by weight of styrene butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3) as a binder, and the slurry composition was coated on a current collector (Al foil), dried at 50°C for 12 hours, and pressed with a roll press device to prepare a positive electrode (at this time, the porosity of the electrode was 65%).
[0064] Lithium-sulfur battery manufacturing The prepared positive electrode and a lithium metal negative electrode having a thickness of 150 μm were placed facing each other, a polyethylene (PE) separator was interposed between them, and the prepared electrolyte was injected to prepare a coin cell type lithium-sulfur battery. Meanwhile, in manufacturing the battery, the positive electrode was punched out at 15 phi, the polyethylene separator was punched out at 19 phi, and the lithium metal was punched out at 16 phi.
[0065] [Example] Lithium-sulfur battery manufacturing Based on the lithium-sulfur battery manufactured in the above manufacturing example, the ES value (mass of electrolyte (g) / mass of sulfur contained in the positive electrode (g): 2≦ES<3.7) and L (unit: mAh / cm 2 ) values (sulfur loading value for the positive electrode: 2≦L≦2.6) were set to satisfy the following formula 1 (the sulfur loading value for the positive electrode was calculated by measuring the weight of the positive electrode punched out at 15 phi and converting it into a formula).
[0066] [Formula 1] 1≦ES / L≦1.4
[0067] [Comparative Example] Lithium-sulfur battery manufacturing Based on the lithium-sulfur battery manufactured in the above manufacturing example, the ES value (mass (g) of electrolyte / mass (g) of sulfur contained in the positive electrode) in the above formula 1 is set to be outside the range of 2≦ES<3.7, and L (unit: mAh / cm 2 ) value (sulfur loading value for the positive electrode) is set to fall outside the range of 2≦L≦2.6.
[0068] [Experimental Example 1] Power evaluation of lithium-sulfur batteries The lithium-sulfur batteries of the examples and comparative examples were discharged at 2C for 10 seconds at 75% remaining capacity based on the 0.1C discharge capacity, and the resistance was measured through a voltage drop, and the maximum output that can be obtained when discharging to 1.5V was calculated. FIGS. 1 and 2 are graphs showing ES / L values according to sulfur loading values for the positive electrode. As shown in FIG. 1, the ES / L value has an inflection point at about 1 to 1.4, and it can be seen that the increase in output decreases as the ES / L value exceeds 1.4. It was also confirmed that the output is particularly rapidly increased when the L value is 2 and 2.5, and is excellent as the output of the lithium-sulfur battery. On the other hand, as shown in FIG. 2, when the L value is 4 or more, the output value did not reach 2kW / kg at the point where the output rapidly increases. Therefore, it can be seen that the ES / L value is optimally 1≦ES / L≦1.4, and in this case, the L value is preferably within the range of 2≦L≦2.6.
[0069] [Experimental Example 2] Energy density and power evaluation of lithium-sulfur batteries. The lithium-sulfur batteries of the examples and comparative examples were discharged at 2C for 10 seconds at 75% remaining capacity based on the 0.1C discharge capacity, and the resistance was measured through a voltage drop, and the maximum output (unit: kW / kg) that can be obtained when discharging to 1.5V was calculated based on the result, and the results are shown in Table 1 below. In addition, the lithium-sulfur batteries of the examples and comparative examples were measured when discharging at 0.1C (lower limit voltage of 1.7V) and then the energy density per weight (unit: Wh / kg) was measured by dividing it by the weight of the cell, and the results are shown in Table 2 below. Figure 3 is a graph showing the energy density and output of the lithium-sulfur battery in relation to the ES / L value, and Figure 4 is a graph showing the output of the lithium-sulfur battery in relation to the ES / L value.
[0070] [Table 1]
[0071] [Table 2]
[0072] As described above, it was confirmed through Experimental Example 1 related to the output of the lithium-sulfur battery that the ES / L value is optimally 1≦ES / L≦1.4, and that the L value at this time is preferably within the range of 2≦L≦2.6. In addition, as shown in Tables 1 and 2 and as shown in Figures 3 and 4, it can be seen that the ES / L value and the L value are preferably within the above ranges when looking at the energy density of the lithium-sulfur battery. Specifically, if the L value is 2≦L<2.5, the energy density of the battery is 300Wh / kg or more and less than 350Wh / kg, and the output value at this time is 2 to 2.6kW / kg. Also, if the L value is 2.5≦L≦2.6, the energy density of the battery is 300 to 350Wh / kg, and the output value at this time is more than 2kW / kg to 2.6kW / kg. In addition, if the ES / L value is 1 and the L value is 2.5≦L≦2.6, the energy density of the battery is 350Wh / kg, and the output value at this time is more than 2kW / kg to 2.3kW / kg.
[0073] Therefore, when the ES value is within the range of 2≦ES<3.7 and the L value is within the range of 2≦L≦2.6, if the ES / L value satisfies 1≦ES / L≦1.4, the weight energy density of the lithium-sulfur battery will be 300Wh / kg or more, and at the same time, the maximum output will be 2kW / kg or more, which is the normally required output, thereby achieving the object of the present invention.
Claims
1. A lithium-sulfur battery comprising a positive electrode containing sulfur as a positive electrode active material, a lithium metal negative electrode, and an electrolyte, wherein the positive electrode active material contains a sulfur-carbon composite and satisfies the following formula 1: [Formula 1] 1≦ES / L≦1.4 In Equation 1, ES is the mass (g) of the electrolyte divided by the mass (g) of sulfur contained in the positive electrode, and L is the sulfur loading value for the positive electrode, expressed in mAh / cm. 2 It is.
2. 2. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery has an energy density of 300 Wh / kg or more and a maximum output of 2 kW / kg or more.
3. 2. The lithium-sulfur battery of claim 1, wherein the ES value is 2≦ES<3.
7.
4. 4. The lithium-sulfur battery of claim 3, wherein the L value is 2≦L≦2.
6.
5. 5. The lithium-sulfur battery of claim 4, wherein the L value is 2≦L<2.5, the energy density of the battery is 300 Wh / kg or more and less than 350 Wh / kg, and the output value is 2-2.6 kW / kg.
6. 5. The lithium-sulfur battery of claim 4, wherein the L value is 2.5≦L≦2.6, the energy density of the battery is 300-350 Wh / kg, and the output value is more than 2 kW / kg to 2.6 kW / kg.
7. 7. The lithium-sulfur battery of claim 6, wherein the ES / L value is 1, the L value is 2.5≦L≦2.6, the energy density of the battery is 350Wh / kg, and the output value at this time is more than 2kW / kg to 2.3kW / kg.
8. 2. The lithium-sulfur battery of claim 1, wherein the positive electrode comprises a positive electrode active material and a binder, and does not comprise a conductive material.
9. 2. The lithium-sulfur battery of claim 1, wherein the sulfur is contained in an amount of 60% to 80% by weight based on the total weight of the positive electrode.
10. 2. The lithium-sulfur battery of claim 1, wherein the electrolyte comprises: a first solvent including a heterocyclic compound including one or more double bonds and at the same time including one or more of an oxygen atom and a sulfur atom; a second solvent including one or more of an ether-based compound, an ester-based compound, an amide-based compound, and a carbonate-based compound; and a lithium salt.
11. 2. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery is an aircraft battery used in Urban Air Mobility (UAM).
Citation Information
Patent Citations
Positive electrode activator for lithium-sulfur battery, lithium-sulfur battery, and electronic product
JP2004119367A
Lithium-sulfur battery with high specific energy
JP2009510684A
Lithium-sulfur battery
JP2019522316A
Lithium secondary battery
KR1020210088025A
Lithium secondary battery
KR1020210100313A